PENGARUH LATIHAN KOORDINASI BERLARI DENGAN LUTUT TINGGI DAN DIIKUTI DENGAN SPRINT TERHADAP KECEPATAN LARI 50 M PADA ATLIT SPRINT 100 M PPLP RIAU - Taufik hidayat; Drs. Ramadi, S.Pd, M.Kes '; Ardiah Juita, S.Pd, M.Pd (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT : A problem of this research was “is there any effect of running coordination exercise with high knee and followed by sprint on the running speed 50 m of the athletes sprint 100 m of PPLP Riau”. a type of this research was experiment research, by using a sampling total technique. 6 people sample was taken the research data was obtained and collected by a pree test and a post test of running 50 m. the result of data was obtained and analyzed statiscally, so the test of hypothesis had been proposed based on the problem : “there is an effect of running coordination excercaise with high knee and followed by sprint (X) on the running speed 50 m of the athlete sprint 100 m of PPLP Riau (Y). based on t value – test analysis as 8.88 and t table as 2,02 means t value > t table. So it can be concluded that Ha is accepted and Ho is rejected. In line with explanation above, it can be stated that there is any significan effect of running coordination excercaise with high knee and followed by sprint on the running speed 50 m of the athlete sprint 100 m of PPLP Riau.Keyword : coordination, speed run